Antipathy for Heidelberg, sympathy for Freiburg? Vincent Ostrom on Max Weber, Walter Eucken, and the compound history of order - Stefan Kolev (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2019)
Vincent Ostrom's legacy is revisited in this paper along three dimensions: Ostrom's contributions as a historian of politico-economic thought, as a complexity theorist, and as an epistemologist. All three dimensions are captured from a perspective which has seldom been studied systematically before: The paper reconstructs Ostrom as a reader and interpreter of German politico-economic thought, especially of Max Weber's theory of bureaucracy and of Walter Eucken's theory of social and epistemic orders. The systems of these two German social scientists embody for Ostrom the two types of social order central to his own typology. The paper incorporates archival sources from the Elinor and Vincent Ostrom Papers, including unpublished papers and correspondence with German social scientists he met during the Ostroms' 1981/1982 stay at Bielefeld University's Center for Interdisciplinary Research (ZiF). Overall, this narrative focuses on what Ostrom called in his reception of the Freiburg School "Eucken's challenge": A set of inquiries about the relevance of political economy for the study of polycentric orders.
Keywords: A12; B25; B41; D73; H11; H41; Z13; 330; Bloomington School; Freiburg School; political theory; history of economics; economic sociology; polycentricity; epistemology